Causal association between psoriasis vulgaris and bullous pemphigoid: a two-sample bidirectional Mendelian randomization study - Zhang, Aobei; Yang, Zhihui; Huang, Tao; Wang, Mingyue (Frontiers in Immunology, 2024)
The association between psoriasis vulgaris and bullous pemphigoid (BP) remains largely unknown.Objectives: To investigate whether there is a causal effect between psoriasis vulgaris and BP.Methods: Two-sample bidirectional Mendelian randomization (MR) analyses were conducted using publicly released genome-wide association studies (GWAS) summary statistics. The GWAS summary statistics for BP were downloaded online from FinnGen Biobank Documentation of the R12 release, which includes 219 BP cases and 218,066 controls. The GWAS data for psoriasis vulgaris were extracted from Sakaue et al., which comprises 5072 cases and 478,102 controls. Single-nucleotide polymorphisms (SNPs) associated with exposure were selected as instrumental variables by performing additional quality control steps. The inverse-variance-weighted (IVW) method was used for the primary MR analyses, and the MR-Egger regression, weighted mode method, weighted median method, and simple mode were employed for sensitivity analyses. The MR-Egger intercept test and "leave-one-out" sensitivity analysis were performed to evaluate the horizontal pleiotropy and the potentially influential SNPs, respectively.Results: Genetically determined log odds of psoriasis vulgaris were associated with an increased risk